Impact of nickel–titanium super-elastic material properties on the mechanical performance of self-expandable transcatheter aortic valves. (February 2023) - Carbonaro, Dario; Zambon, Sara; Corti, Anna; Gallo, Diego; Morbiducci, Umberto; Audenino, Alberto L.; Chiastra, Claudio
Abstract: Self-expandable transcatheter aortic valves (TAVs) elastically resume their initial shape when implanted without the need for balloon inflation by virtue of the nickel–titanium (NiTi) frame super-elastic properties. Experimental findings suggest that NiTi mechanical properties can vary markedly because of a strong dependence on the chemical composition and processing operations. In this context, this study presents a computational framework to investigate the impact of the NiTi super-elastic material properties on the TAV mechanical performance. Finite element (FE) analyses of TAV implantation were performed considering two different TAV frames and three idealized aortic root anatomies, evaluating the device mechanical response in terms of pullout force magnitude exerted by the TAV frame and peak maximum principal stress within the aortic root. The widely adopted NiTi constitute model by Auricchio and Taylor (1997) was used. A multi-parametric sensitivity analysis and a multi-objective optimization of the TAV mechanical performance were conducted in relation to the parameters of the NiTi constitutive model. The results highlighted that: five NiTi material model parameters ( E A, σ t L S, σ t U S, σ t U E and σ c L S ) are significantly correlated with the FE outputs; the TAV frame geometry and aortic root anatomy have a marginal effect on the level of influence of each NiTi material parameter; NiTi alloy candidates with pareto-optimal characteristics in terms of TAV mechanical performance can be successfully identified. In conclusion, the proposed computational framework supports the TAV design phase, providing information on the relationship between the super-elastic behavior of the supplied NiTi alloys and the device mechanical response. Graphical abstract: Image 1 Highlights: FE analyses of the implantation of TAVs in different aortic root scenarios. Sensitivity analysis of NiTi material parameters on TAV mechanical performance. Multi-objective optimization of NiTi material parameters of the TAV frame. E A, σ t L S, σ t U S, σ t U E and σ c L S showed non-negligible correlations with the FE outputs. Influence of NiTi material parameters is independent of anatomy and TAV geometry.